Effect of Horizontal Strabismus Surgery on the Refractive Status. (3rd July 2015) - Al-Tamimi, Elham; Al-Nosair, Ghadah; Yassin, Sanaa
Abstract: Purpose : To evaluate the effects of horizontal strabismus surgery on the refractive and astigmatic status of eyes following horizontal muscle surgery using double-angle vector analysis. Materials and Methods : This was a retrospective analysis of 137 patients (250 eyes) conducted between February 1997 and October 2010 in patients who had unilateral or bilateral recession or monocular recession and/or underwent resection of horizontal muscles by a single surgeon. Refraction data were obtained at 1–2 weeks preoperative and at 4–6 weeks and 4–6 months postoperative. Surgically induced refractive changes were calculated using double-angle vector analysis. Results : The mean change in the spherical equivalent (SE) of the refraction was 0.23 ± 0.78 D for surgically induced refractive changes at 4–6 weeks postoperative (SIRC1; p  < 0.0001) and 0.14 ± 0.85 D ( p  = 0.018) for surgically induced refractive changes at 4–6 months postoperative (SIRC2), indicating a small shift in the myopic direction with regression at 4–6 months. The mean amplitudes of the induced cylinders were 0.072 ± 1.22 D ( p  = 0.262) in SIRC1 and 0.20 ± 1.14 D ( p  = 0.012) in SIRC2, and the mean axis of the induced plus cylinder was 21.74° in SIRC1, indicating a small shift in the with-the-rule direction, but no statistically significant difference from zero ( p  = 0.331). The changes in the surgically induced refraction over time (SIRC d), ie, 0.05 ± 0.64 in SE ( p  = 0.255) and 0.09 ± 0.65 in the cylinder ( p  = 0.049), were stable. There was no significant correlation between the amounts of horizontal rectus muscle recession and/or resection and the cylinder power of individual induced astigmatism at 4–6 weeks after surgery ( p  = 0.266) and the myopic shift ( p  = 0.345). Moreover, there were no significant correlations between the ages of the patients and the spherical equivalent for SIRC1 ( p  = 0.858) and the induced cylinder for SIRC1 ( p  = 0.750). Conclusion : Horizontal rectus muscle surgery tended to induce a transient, statistically significant change in the spherical equivalent of refraction, with a myopic shift that was clinically not important. Our findings did not strongly support that the astigmatism induced changes. There was no correlation between the amount of recession and/or resection and the amount of induced refractive error .